Development Of Controller For Back Cover Assembly Station For Flexible Manufacturing System Using Programmable Logic Controller (PLC) - Aminuddin, Abdul Wahab (UTeM, 2008)
Flexible Manufacturing System (FMS) is manufacturing technology. The problem in the world of manufacturer is to achieve "agility". An agile manufacturer is one who is the fastest to the market, operates with the lowest total cost and has the greatest ability to "delight" its customers. FMS is simply one way that manufacturers are able to achieve this agility. Beside that, the problem in this project is to develop the controller for FMS system. In this project, there are two objective needs to be achieved which are to automate assembly station and to develop and install the programming of Programmable Logic Controller (PLC) to control the FMS system for LCD assembly. Methodology have been used in this project is start with the planning, followed by literature review, continued with analyzing, design and modification, and implementation phase. The controller have been programmed to operate as required in order to automate the assembly station.